Prevalence of Permanent Congenital Hypothyroidism in Isfahan-Iran - Hashemipour, Mahin (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Considering the importance to determine the reasons for the higher occurrence of congenital hypothyroidism (CH) in Iran, in this study we report the prevalence of permanent CH (PCH) in Isfahan province 7 years after initiation of CH screening program in Isfahan. METHODS: In this cross-sectional study, children with a primary diagnosis of CH studied. They clinically examined and their medical files were reviewed by a pediatric endocrinologist. Considering screening and follow-up lab data, radiologic findings and the decision of pediatric endocrinologists the final diagnosis of PCH was determined. RESULTS: A total of 464,648 neonates screened in Isfahan province. The coverage percent of the CH screening and recall rate was 98.9% and 2.1%, respectively. A total of 1990 neonates were diagnosed with primary CH. PCH was diagnosed in 410 neonates. The prevalence of PCH and transient CH (TCH) was 1 in 1133 and 1 in 294 live births. The most common etiology of CH was thyroid dyshormonogenesis. CONCLUSIONS: Though the prevalence of PCH is high, but the higher prevalence of CH in Isfahan is commonly due to cases with TCH. Hence, the necessity of determining new strategies for earlier diagnosis of patients with TCH is recommended.